GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN KEBERLANJUTAN SEBAGAI PENENTU NILAI PERUSAHAAN: ANALISIS MODERASI KEPEMILIKAN INSTITUSIONAL - Zidani Arhandi Rahmana; Jeni Wardi; Indarti Indarti (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the influence of sustainability disclosure, the proportion of independent commissioners, institutional ownership, and the interaction between sustainability disclosure and institutional ownership on firm value in plantation companies listed on the Indonesia Stock Exchange during 2021–2024. Using a quantitative panel data regression approach with purposive sampling, the findings reveal that sustainability disclosure positively influences firm value, while independent commissioners and institutional ownership show no significant effect. Moreover, institutional ownership does not moderate the relationship between sustainability disclosure and firm value. A key contribution of this research is the evidence that the combination of sustainability disclosure and institutional ownership has not yet generated tangible added value, highlighting that governance effectiveness depends on disclosure quality and industry sensitivity. The study underscores the importance of enhancing sustainability disclosure, strengthening the role of independent commissioners, and engaging institutional ownership in strategic oversight to foster legitimacy and stakeholder trust.